Enhancing Spare Parts Inventory Control in Automotive SMEs: A Digital Approach with Google Tools Integration - Mohamad Khairi Hassan,; Mohd Hazri Mohd Rusli,; Suzilawati Kayat,; Wan Muhammad Azim Wan Mokhtar, (International Journal of Integrated Engineering, 2025)
Smooth operation of manufacturing processes is critical for maintaining production efficiency, and machine downtime can significantly disrupt operations, leading to substantial financial losses. One of the primary contributors to extended downtime is the unavailability of replacement parts due to inadequate spare parts management. Traditional manual inventory control often results in unclear spare part statuses, leading to stockouts and further production delays. This study aims to digitalize and optimize spare parts inventory management for small and medium-sized enterprises (SMEs) in the automotive sector by developing an integrated system using Google-based tools. The system leverages Google Sheets as the central database, AppSheet for mobile-based data input and transaction management, and Looker Studio for real-time visualization of inventory status through interactive dashboards. Key features of the system include stock level alerts, barcode scanning for faster data entry, and predictive analytics for demand forecasting. The integration of these tools creates a cohesive system that eliminates manual record-keeping, enhances the accuracy of spare parts tracking, and prevents issues such as stockouts and overstocking. Additionally, the system allows easy access to critical information, including supplier details, pricing, and specifications. Through effective spare parts management, the system not only reduces machine downtime but also optimizes operational costs and improves decision-making processes in inventory management, contributing to more efficient and cost-effective manufacturing operations.